2021
DOI: 10.1051/0004-6361/202140347
|View full text |Cite
|
Sign up to set email alerts
|

An intriguing globular cluster in the Galactic bulge from the VVV survey

Abstract: Context. Globular clusters (GCs) are the oldest objects known in the Milky Way, so each discovery of a new GC is astrophysically important. In the inner Galactic bulge regions these objects are difficult to find due to extreme crowding and extinction. However, recent near-IR surveys have discovered a number of new bulge GC candidates that need to be further investigated. Aims. Our main objective is to use public data from the Gaia mission, the VISTA Variables in the Via Lactea (VVV) survey, the Two Micron All … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…We added a black circle and arrow in each panel in order to highlight the over-density, which indicates the presence of the cluster. Garro et al (2022b), FSR 19 and FSR 25 (Obasi et al 2021), and Minni48 (Minniti et al 2021c); and another five GCs confirmed in Garro et al (2022a). These studies as well as other ones are fundamental since they can contribute, from a broad point of view, for one to understand the formation and evolution of the MW GC system.…”
Section: Introductionmentioning
confidence: 71%
“…We added a black circle and arrow in each panel in order to highlight the over-density, which indicates the presence of the cluster. Garro et al (2022b), FSR 19 and FSR 25 (Obasi et al 2021), and Minni48 (Minniti et al 2021c); and another five GCs confirmed in Garro et al (2022a). These studies as well as other ones are fundamental since they can contribute, from a broad point of view, for one to understand the formation and evolution of the MW GC system.…”
Section: Introductionmentioning
confidence: 71%
“…sons: (i) PMs ensure the stars in the cluster are divided better from the stars in the field since a cluster is expected to share coeval motions; (ii) as demonstrated by Garro et al (2021c) and Minniti et al (2021c), this method substantially reduces the percentage of contaminants better than the statistical decontamination procedure, excluding stars with disk-like PMs. For this purpose, we constructed the VPM diagrams as a 2D histogram shown in Fig.…”
Section: Decontamination Procedures and Cluster Membershipmentioning
confidence: 99%
“…The Gaia mission (e.g. Cantat-Gaudin et al 2019;Castro-Ginard et al 2020) is extremely helpful in that endeavour and has in fact confirmed many of the recently discovered star clusters as GCs, some examples include the following: Garro 01 (Garro et al 2020), FSR 1758 (Barbá et al 2019;Villanova et al 2019;Romero-Colmenares et al 2021), Patchick 99 (Garro et al 2021c), Patchick 125 (Fernández-Trincado et al 2022;Garro et al 2021a, named also Gran 3 by Gran et al 2022), and VVV-GC160 (Minniti et al 2021a;Garro et al 2021d); another nine GCs confirmed by Garro et al (2021d), FSR 19 and FSR 25 (Obasi et al 2021), and Minni48 (Minniti et al 2021c); and another five GCs confirmed in Garro et al (2021a). These studies as well as other ones are fundamental since they can contribute, from a broad point of view, for one to understand the formation and evolution of the MW GC system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, towards the innermost regions the differential reddening becomes more prominent increasing the uncertainties in the determination of distances. Then, the extinction and distances are estimated following the same procedures described in our previous works e.g., Garro et al 2021b andMinniti et al 2021b. We adopt existing reddening maps, such as those by Gonzalez et al (2011), Soto et al (2019 and Surot et al (2019) in the NIR and by Schlafly & Finkbeiner (2011) in the optical passbands.…”
Section: Estimation Of Physical Parametersmentioning
confidence: 99%
“…Significant effort has been devoted in the last years to studying the real nature of GC candidates and indeed many of them have been confirmed. A few examples are VVV-CL001 (Minniti et al 2011;Fernández-Trincado et al 2021b), VVV-CL002 and VVV-CL003 (Moni Bidin et al 2011), FSR 1716Minniti et al 2017b), RLGC 1 and 2 (Ryu & Lee 2018), Camargo 1107, 1108, and 1109(Camargo & Minniti 2019, FSR 1758 (Barbá et al 2019;Romero-Colmenares et al 2021), Garro 01 (Garro et al 2020), UKS 1 (Fernández-Trincado et al 2020), Patchick 99 (Garro et al 2021b), FSR 19 and FSR 25 (Obasi et al 2021), VVV-CL160 (Minniti et al 2021a), Minni 48 (Minniti et al 2021b), FSR 1776Dias et al 2021), Ton 1 (Fernández-Trincado et al 2021, in press), and other 9 GCs in Garro et al (2021c).…”
Section: Introductionmentioning
confidence: 99%